Synthesis of Well‐Crystallized, High‐Performance LiNi0.5Mn1.5O4 Octahedra as Lithium‐Ion‐Battery Electrode Promoted by Metal Manganese Powders. Issue 3 (26th August 2016) - Liu, Haiqiang; Jiang, Yi; Tan, Xinghua; Chen, Jiankun; Guo, Yanjun; Wang, Hanfu; Chu, Weiguo
Abstract: Metal Mn powders instead of conventional Mn salts were used for the first time tried as a Mn source to synthesize high‐performance LiNi0.5 Mn1.5 O4 (M‐LNMO) using a sol–gel method. Mn powders promote the formation of well‐crystallized octahedra with the Fd 3 m spinel structure. M‐LNMO has a lower stress, a slightly smaller lattice constant, which arises from the lower amount of Mn 3+ because of the lower oxygen deficiency, a higher cation ordering, and longer Li−O and shorter Mn (Ni)−O bonds than LiNi0.5 Mn1.5 O4 synthesized from manganese acetate (MA‐LNMO). The well‐crystallized octahedra, the low stress, the low amount of Mn 3+, and the long Li−O and short Mn (Ni)−O bonds for M‐LNMO result in its excellent performance such as a discharge capacity of 68 mAh g −1 at 50 C and a capacity retention of 90 % after 600 cycles at 10 C. This study raises the possibility to promote the synthesis of high‐performance LiNi0.5 Mn1.5 O4 for mass production by using cheap and simple Mn sources such as Mn powders. Abstract : Crystal clear : LiNi0.5 Mn1.5 O4 is synthesized by using Mn metal: the product, M‐LNMO, is composed mostly of octahedral crystals enclosed with {1 1 1} planes with an excellent crystallinity. The morphology of the octahedral crystals along with the low stress, the low concentration of Mn 3+, and the long Li−O and short Mn (Ni)−O bonds account for the excellent electrochemical performance of M‐LNMO.